Leadership styles and employee engagement at Ghana Education Service, Central Region - Nyarko, Emelia (University of Cape Coast, 2024)
This study aimed at examining the effect of leadership styles on employee engagement in Ghana Education Service. Three specific objectives were stated. These objectives were; to assess the level of engagement among staffs in the Ghana Education Service; to examine the leadership style utilized by management of the Ghana Education Service; to analyse the effect of leadership style on employee engagement at the Ghana Education Service. Centered around trait theory and employed explanatory design to test the relationships between different variables. Data was collected through questionnaires, and a quantitative approach was employed for analysis. A simple random sampling technique selected 340 respondents. To analyze the data, both multiple regression and descriptive statistics were used. The study revealed that employees are enthusiastic about spending their entire careers with the organisation and perceive the institution‘s challenges as their own. They feel a strong sense of belonging and family within the institution, experience physical energy while working, and find that time passes quickly during work hours. Additionally, employees are highly focused on their tasks and work longer hours, finding it challenging to detach from their work. The research found that transformational leadership was the predominant style used by the management of the Ghana Education Service. Transformational, democratic, laissez-faire, and transactional leadership styles all had a positive and significant impact on employee engagement, whereas autocratic leadership style had a negative but significant effect. The study recommended that policy makers should engage leaders on how appropriate leadership style can enhance employee engagement.
xi, 79p;, ill